2017
DOI: 10.1186/s40795-017-0206-7
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation and socio-demographic correlates of taste preferences in European children

Abstract: Background: Studies on aggregation of taste preferences among children and their siblings as well as their parents are scarce. We investigated the familial aggregation of taste preferences as well as the effect of sex, age, country of residence and education on variation in taste preferences in the pan-European I.Family cohort. Method: Thirteen thousand one hundred sixty-five participants from 7 European countries, comprising 2,230 boys <12 years, 2,110 girls <12 years, 1,682 boys ≥12 years, 1,744 girls ≥12 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…The food and beverages included in our analyses were chosen based on factor analyses conducted by Jilani and colleagues [55] that assigned foods to respective taste modalities. In accordance with the factor analyses, we computed scores for the liking of three specific taste modalities: sweet, fatty and bitter, by calculating the mean liking of the foods and drinks included in each of the 3 categories.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The food and beverages included in our analyses were chosen based on factor analyses conducted by Jilani and colleagues [55] that assigned foods to respective taste modalities. In accordance with the factor analyses, we computed scores for the liking of three specific taste modalities: sweet, fatty and bitter, by calculating the mean liking of the foods and drinks included in each of the 3 categories.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the parents of half of our sample had a high educational status, a fact which might also bias the results with regard to socio-economic status. In addition, we did not have information on other confounding factors such as the role of the maternal diet during breastfeeding and the family diet, factors that have been found to influence taste preference and food intake in children [3,55,74]. Lastly, our research was conducted using only cross-sectional data enriched with retrospective information.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Previous research has highlighted that other factors such as familiarity showed to significantly affect children's liking as children will eat what they like, and like what they know [91,92]. Extrinsic factors such as the family's socioeconomic and cultural background have been reported to also provide a significant effect on children's food liking [93]. Moreover, in our study, taste sensitivity was measured using a water solution sample, but food liking was measured by a stated liking (without tasting) in a questionnaire.…”
Section: Children's Taste Sensitivity and Food Likingmentioning
confidence: 99%
“…The associations of sweet taste preference with fruit consumption and of bitter taste preference with vegetable consumption and the relationship between sweet taster status and sweet preference were analyzed as well. Foods to asses taste preferences were chosen according to Hungarian dietary patterns ( 39 ) and well-known and available food items in the Roma population ( 40 ) ( Table 1 ). Factors influencing taste and food preferences and dietary patterns were registered, such as smoking ( 41 – 43 ) heavy alcohol use ( 44 ) and special diet adherence.…”
Section: Methodsmentioning
confidence: 99%